2019
DOI: 10.3389/fpsyt.2019.00680
|View full text |Cite
|
Sign up to set email alerts
|

Altered Patterns of the Fractional Amplitude of Low-Frequency Fluctuation and Functional Connectivity Between Deficit and Non-Deficit Schizophrenia

Abstract: Objective: A limited number of studies have previously reported on the regional activity [amplitude of low-frequency fluctuation (ALFF)] and functional integration [functional connectivity (FC)] of the whole brain in deficit schizophrenia (DS). The present study investigates the resting-state characteristics of the fractional ALFF (fALFF) and the FC in both DS and non-deficit schizophrenia (NDS) patients, and further explores their correlations with neurocognitive features. Methods: Demographic, resting-state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 48 publications
3
23
1
Order By: Relevance
“…In addition, some studies have found that the insula plays a regulatory role in the activation vs. inactivation states of the CEN and the DMN. Therefore, structural and functional changes in the insula may have participated in the onset and progression of schizophrenia (47). In the present study, our main observations were decreased FC between the left SFG and insula.…”
Section: Discussionsupporting
confidence: 48%
“…In addition, some studies have found that the insula plays a regulatory role in the activation vs. inactivation states of the CEN and the DMN. Therefore, structural and functional changes in the insula may have participated in the onset and progression of schizophrenia (47). In the present study, our main observations were decreased FC between the left SFG and insula.…”
Section: Discussionsupporting
confidence: 48%
“…In line with this hypothesis, areas like the posterior cingulate cortex (PCC) that exhibit high resting state metabolism in PET scans also have higher ALFF and fALFF than other cortical areas (Zou et al, 2008). Furthermore, these measures of low frequency power can discriminate between patient groups and healthy controls or between rest and task performance (Zang et al, 2007;Cui et al, 2019;Li et al, 2019;Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 79%
“…major depressive disorder, schizophrenia, attention-deficit/hyperactivity disorder and addiction) and neurodegenerative diseases (e.g. Alzheimer's disease and frontotemporal dementia) to detect neural activity (40,41,60,61). However, very few studies have previously examined the effect of bariatric surgery on spontaneous neural activity as assessed with fALFF or ReHo (30,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%